Modifiable variables affecting interdialytic weight gain include dialysis time, frequency, and dialysate sodium. Issue 4 (18th June 2013) - Thomson, Benjamin K. A.; Dixon, Stephanie N.; Huang, Shi‐Han S.; Leitch, Rosemary E.; Suri, Rita S.; Chan, Christopher T.; Lindsay, Robert M.
Abstract: Interdialytic weight gain (IDWG) is associated with hypertension, left ventricular hypertrophy, and all‐cause mortality. Dialysate sodium concentration may cause diffusion gradients with plasma sodium and influence subsequent IDWG. Dialysis time and frequency may also influence the outcomes of this Na + gradient; these have been overlooked. Our objective was to identify modifiable factors influencing IDWG. We performed a retrospective multivariable regression analyses of data from 86 home hemodialysis patients treated by hemodialysis modalities differing in frequency and session duration to determine factors involved that predict IDWG. Age, diabetic status, and residual renal function did not correlate with IDWG in the univariable analysis. However, using a combination of backwards selection and Akaike information criterion to build our model, we created an equation that predicted IDWG on the basis of serum albumin, age, patient sex, dialysis frequency, and the diffusive balance of sodium, represented by the product of the duration of dialysis and the patient plasma to dialysate Na + gradient. This equation was internally validated using bootstrapping, and externally validated in a temporally distinct patient population. We have created an equation to predict IDWG on the basis of independent factors readily available before a dialysis session. The modifiable factors include dialysis time and frequency, and dialysate sodium. Patient sex, age, and serum albumin are also correlated with IDWG. Further work is required to establish how improvements in IDWG influence cardiovascular and other clinical outcomes.